Pengaruh pengalaman Pelanggan dan Cita Rasa terhadap Kepuasan pelanggan pada Cake Boss Deltasari Indah Waru Sidoarjo - Fitri A’isya; Awin Mulyati; Diana Juni Mulyati (Politeknik Kampar, 2025)
The culinary industry continues to experience positive growth, although the increase is not particularly significant. This condition requires business actors to continuously improve product and service quality in order to achieve customer satisfaction. This study aims to analyze the influence of Customer Experience and Taste on customer satisfaction at Cake Boss Deltasari Indah Waru Sidoarjo. A quantitative approach was used with a survey method, utilizing questionnaires distributed to 100 respondents who had made at least two purchases. The results of data analysis show that both customer experience and taste have a significant partial effect on customer satisfaction. Simultaneously, these two variables also have a significant influence on the level of satisfaction. However, among the two variables, taste was found to have the most dominant influence on customer satisfaction. This indicates that the taste quality of the product plays a crucial role in shaping customer satisfaction levels. These findings suggest that continuous improvement in the shopping experience and taste quality can serve as an effective strategy to enhance customer satisfaction in the culinary sector.